1982
DOI: 10.1203/00006450-198204000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Changes and Hemoglobin Analysis in β Thalassemia Heterozygotes during the First Year of Life

Abstract: SummaryWe have studied the hematology and hemoglobin patterns of normal and heterozygous j3 thalassemia infants in serial samples obtained during the first year of life. The hemoglobin level, mean cell volume and mean cell hemoglobin were significantly lower in the j3 thalassemia traits by the age of 3 months and this difference was maintained throughout the first year. Hb A2 levels were significantly higher in the j3 thalassemia group but increased in both groups throughout the first year. Hb F levels were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…On the contrary to Hb F, a trend toward increased Hb A 2 expression during 6‐23 months of age was observed though statistical significance was not reached during 12‐18 months of age. Similarly, results from an earlier study that followed the changes in Hb A 2 levels in normal and β‐thal heterozygotes showed a gradually increased Hb A 2 during the first year of life . These findings suggest that, despite the low expression, the δ‐globin gene may remain active during the first two years of life.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…On the contrary to Hb F, a trend toward increased Hb A 2 expression during 6‐23 months of age was observed though statistical significance was not reached during 12‐18 months of age. Similarly, results from an earlier study that followed the changes in Hb A 2 levels in normal and β‐thal heterozygotes showed a gradually increased Hb A 2 during the first year of life . These findings suggest that, despite the low expression, the δ‐globin gene may remain active during the first two years of life.…”
Section: Discussionsupporting
confidence: 65%
“…the first year of life. 22 These findings suggest that, despite the low expression, the δ-globin gene may remain active during the first two years of life. Similar to that observed in adults, 7,10,23 the levels of Hb E were affected by the α-thal coinheritance.…”
Section: Discussionmentioning
confidence: 95%
“…We used HPLC to identify hemoglobin variants, to exclude ΒΤΤ in children aged 3–6 months when HbA 2 < 3.0% and to diagnose BTT in those aged >6 months when HbA 2 > 3.6%. Samples from patients below the age of 3 months were not eligible for inclusion, as HbA 2 is not fully developed at this age and, therefore, cannot be used to rule out BTT . When HbA 2 was in the range 3.2–3.6% and a β + ‐thalassemia was suspected, sequencing of the β‐globin gene was performed by the Department of Medical Genetics (DMG) at Oslo University Hospital Ullevaal, Norway ( n = 2).…”
Section: Methodsmentioning
confidence: 99%
“…Three recent prospective studies have shown that DFX is effective in removing iron from the heart (increase in cardiac T2*), although the LVEF remained unchanged 84,85. In one of these studies, the reduction in cardiac iron was observed mainly in patients with mild to moderate liver siderosis 86. DFX did not reduce the iron in the heart of patients who had excessive liver iron overload (usually > 30 mg/g dw).…”
Section: The Evaluation Of Iron Burdenmentioning
confidence: 98%